1991
DOI: 10.1073/pnas.88.9.4025
|View full text |Cite
|
Sign up to set email alerts
|

Local production of tumor necrosis factor encoded by recombinant vaccinia virus is effective in controlling viral replication in vivo.

Abstract: Tumor necrosis factor (TNF) has pleiotropic effects on a wide variety of cell types. In vitro studies have demonstrated that TNF has antiviral properties and is induced in response to viral infections. However, a role for TNF in the antiviral immune response of the host has yet to be demonstrated. Here we describe the construction of and studies using a recombinant vaccinia virus that encodes the gene for murine TNF-a. By comparing the replication ofand immune responses elicited by the TNF-encoding virus to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 38 publications
2
60
0
Order By: Relevance
“…However, our studies also indicated that IFN~: is not the only cytokine involved in virus clearance from salivary glands. The search for such a cytokine focused on TNF~, which has been implicated in a number of parasitic (Havell, 1987;Titus et al, 1989;Chen et al, 1992;Johnson, 1992;Silva & Faccioli, 1992), viral (Rossol-Voth et aI., 1991Sambhi et al, 1991) and bacterial infections (Nauciel & Espinase-Maes, 1992). TNF~ is a pluripotent cytokine with a variety of biological properties and is produced by many cell types, but mostly by activated macrophages (Larrick & Wright, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, our studies also indicated that IFN~: is not the only cytokine involved in virus clearance from salivary glands. The search for such a cytokine focused on TNF~, which has been implicated in a number of parasitic (Havell, 1987;Titus et al, 1989;Chen et al, 1992;Johnson, 1992;Silva & Faccioli, 1992), viral (Rossol-Voth et aI., 1991Sambhi et al, 1991) and bacterial infections (Nauciel & Espinase-Maes, 1992). TNF~ is a pluripotent cytokine with a variety of biological properties and is produced by many cell types, but mostly by activated macrophages (Larrick & Wright, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…TNF is directly cytotoxic to cells infected with both DNA and RNA viruses (29,30), and overexpression of the cytokine by a recombinant vaccinia virus leads to rapid virus clearance from infected mice (31). The TNF superfamily of cytokines and receptors can activate nuclear factor B and effect cell growth, differentiation, or death.…”
Section: Hcv Core Protein Inhibits Tnf-␣-induced Cleavage Of Poly-(admentioning
confidence: 99%
“…One of the cytokines secreted by macrophages is TNF-␣. This cytokine plays a beneficial role in clearance of a number of viral infections (2)(3)(4)(5) as well as parasitic and bacterial infections (6 -10). In contrast, TNF-␣ is also involved in the immunopathology of diseases such as diabetes, hepatitis, and rheumatoid arthritis (11)(12)(13)(14).…”
mentioning
confidence: 99%